PENERAPAN METODE FORWARD CHAINING DAN CERTAINTY FACTOR UNTUK DIAGNOSA PENYAKIT PADA TANAMAN BONSAI - Anita Anita; Rodhy Rodhy; Surya Ningsih; Dumawati Solin (Jurnal Guru Kita PGSD, 2019)
Abstract: Application of Forward Chaining and Certainty Factor Methods for Diagnosing Diseases in Bonsai Plants. Bonsai plants are dwarfed plants which are generally planted in shallow pots. The main element in bonsai is harmony between pots and plants, in addition to harmony between pots and plants there are also other elements such as the size of the trunk, the height of the tree, the spread of roots, twigs, and large leaves. Therefore, planting and maintaining bonsai is quite complicated, where the way to care for bonsai plants ranging from fertilization to formation must be highly considered and very thorough. Expert systems are needed to help quickly find out what diseases attack bonsai plants based on symptoms that arise. Not only the type of disease, this system also informs how to deal with plants affected by the disease and how to prevent it. The results of the application of the Forward Chaining Method and Certainty Factor can provide a diagnosis of pests in bonsai based on the symptoms given. Based on the results of the MySQL calculation is used as a database design, and system design using the programming language Hypertext Preprocessor (PHP).Keywords: Bonsai, Expert System, Forward Chaining, Certainty Factor, PHPAbstrak: Penerapan Metode Forward Chaining dan Certainty Factor untuk Diagnosa Penyakit pada Tanaman Bonsai. Tanaman hias Bonsai adalah sebuah tanaman yang dikerdilkan dimana pada umumnya tanaman ini ditanaman dalam pot yang dangkal. Unsur utama dalam bonsai adalah keharmonisan antara pot dan tanaman, selain keharmonisan antara pot dan tanaman ada juga unsur lainnya seperti besar batang, tinggi pohon, penyebaran akar, ranting, dan besar daun. Oleh karna itu penanaman dan pemeliharaan bonsai cukup rumit, dimana cara merawat tanaman bonsai mulai dari pemupukan sampai pembentukan harus sangat diperhatikan dan sangat teliti. Sistem pakar  di butuhkan untuk membantu mengetahui secara cepat penyakit apa yang menyerang tanaman bonsai berdasarkan gejala yang muncul. Tidak hanya jenis penyakit, sistem ini juga menginformasikan cara penanganan untuk tanaman yang terserang penyakit dan cara pencegahannya. Hasil penerapan Metode Forward Chaining  danCertainty Factor dapat memberikan diagnosa hama pada tanaman bonsai berdasarkan gejala-gejala yang diberikan.  Berdasarkan hasil perhitungan MySQL digunakan sebagai perancangan database, dan perancangan sistem menggunakan bahasa pemrograman Hypertext Preprocessor (PHP). Kata Kunci :Bonsai, SistemPakar, Forward Chaining, Certainty Factor, PHP.